The EnTPACK rubric: development, validation, and reliability of an instrument for measuring pre-service science teachers’ enacted TPACK - Aumann, Alexander; Schnebel, Stefanie; Weitzel, Holger (Frontiers in Education, 2023)
Science instruction can benefit from the use of digital technologies if pre-service teachers are given opportunities to acquire Technological Pedagogical And Content Knowledge (TPACK) as part of their studies. However, the prevailing self-report approach to TPACK measurement does not allow conclusions to be drawn about enacted TPACK, which is rarely assessed in real classroom situations. In addition, instruments designed to measure TPACK enactment lack descriptive clarity and no single instrument is used to assess the three relevant phases of teacher competencies (lesson planning, implementation, and reflection). The present paper addresses this gap by presenting the development and validation of a comprehensive rubric for assessing the enacted TPACK of pre-service science teachers. To operationalize the “fuzzy” aspects of the framework, the rubric targets a specific use of digital media and instructional approach in science teaching: student-generated explainer videos and animations. At the core of the development process is a theory- and literature-based systematic review of (1) existing instruments for assessing pre-service science teachers’ enacted TPACK and (2) instructional criteria for student-generated explainer videos in science classes. The resulting rubric allows valid conclusions given the appropriate conditions, has demonstrated reliability, and excels due to its specific focus, high degree of differentiation, systematic grounding in theory and literature, objective grading criteria, and comprehensive applicability to all three phases of teacher competencies.